2015
DOI: 10.1098/rstb.2014.0126
|View full text |Cite
|
Sign up to set email alerts
|

Light pollution alters the phenology of dawn and dusk singing in common European songbirds

Abstract: Artificial night lighting is expanding globally, but its ecological consequences remain little understood. Animals often use changes in day length as a cue to time seasonal behaviour. Artificial night lighting may influence the perception of day length, and may thus affect both circadian and circannual rhythms. Over a 3.5 month period, from winter to breeding, we recorded daily singing activity of six common songbird species in 12 woodland sites, half of which were affected by street lighting. We previously re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 57 publications
1
92
1
2
Order By: Relevance
“…Over the past 100 years, for example, the nighttime light pollution caused by excessive amounts and indiscriminate diffusion of external lighting has emerged as an important environmental issue because of its adverse effects [2][3][4][5]. To elucidate how repetitive exposure to artificial night lighting affects photosynthetic pigments as a potential indicator of premature leaf senescence as well as yellowing and defoliation in newly initiated leaves, yellow-poplar seedlings were exposed to the natural day/night cycle and the day/night with artificial lighting cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 100 years, for example, the nighttime light pollution caused by excessive amounts and indiscriminate diffusion of external lighting has emerged as an important environmental issue because of its adverse effects [2][3][4][5]. To elucidate how repetitive exposure to artificial night lighting affects photosynthetic pigments as a potential indicator of premature leaf senescence as well as yellowing and defoliation in newly initiated leaves, yellow-poplar seedlings were exposed to the natural day/night cycle and the day/night with artificial lighting cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Nighttime light pollution generated by excessive external lighting has been demonstrated as an important environmental issue caused by adverse effects such as energy waste [1][2][3][4][5]. Notably, despite the fundamental importance of natural darkness, nighttime artificial lighting has become a globally widespread phenomenon causing light pollution [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, light at night is considered as a major driver of change in timing of daily activity. Light pollution effect has been studied mainly during the breeding period and in the context of extended vocal activity associated with displaying behaviour (Miller 2006;Da Silva et al 2015) and earlier development of reproductive system (Kempenaers et al 2010;Dominoni et al 2013). In contrast, the effect of artificial lights on the timing of behaviours during winter has received relatively little attention.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have tried to overcome this limitation in the field to at least separate the effects of noise and light, while controlling for ambient temperature (Kempenaers et al 2010; Da Silva et al 2014. These have shown that light pollution can clearly alter the onset and offset of daily singing in a variety of species, and that the annual development of dawn and dusk chorus is accelerated under artificial lights (Da Silva et al 2015 ). In addition, Kempenaers and colleagues have demonstrated that artificial lights not only advance dawn song in the blue tit, but early singing associated with lights was positively correlated with the amount of extra pair offspring that males were able to sire, hinting at potential reproductive consequences of light pollution (Kempenaers et al 2010 ).…”
Section: Light Pollution and Daily Cyclesmentioning
confidence: 99%